Dao Companion to the Philosophy of the Zhuangzi - Chong, Kim-chong (Dao Companions to Chinese Philosophy, 2022)
1. Introduction(Chong) -- Part 1. Text, Authorship and Zhuangzi -- 2. Authorship of the Zhuangzi(Keung Lo) -- 3. Various Positions on Zhuangzi Scholarship(Klein) -- 4. The Commentarial Tradition on the Zhuangzi(Chai) -- 5. A Portrait of Zhuangzi(Chong) -- Part 2. Central Concepts -- 6. Zhuangzi on ming (命) (Raphals) -- 7. Zhuangzi’s Idea of Being One (weiyi 為一) (Fung) -- 8. Getting and Forgetting Oneness in the Zhuangzi (Ziporyn) -- 9. The Ontology of the Vast and the Minute (daxiao 大小) (Coutinho) -- 10.Transformation of Things and Qi (wuhua 物化, qihua 氣化) (Sato) -- 11. Virtue/Power (de 德) (Chan) -- 12. No Emotions (wu qing 無情) (Chai) -- 13. The Division between Heaven (tian 天) and Human (ren 人) (Perkins) -- 14. Fasting of the Heart-Mind (xin zhai 心齋) (Zhang) -- 15. The True Person (zhen ren 真人) and True Knowledge (真知) (Xu) -- Part 3. Language and Metaphor -- 16. The Language of the Zhuangzi (Porat) -- 17. Yan (言Words) and Yi (意Meaning) (Fang) -- 18. Zhuangzi's conception of Yu Yan (寓言Imputed Words) and Zhi Yan (卮言Goblet Words) (Fried) -- 19. Humor and its Philosophical Significance in the Zhuangzi (Moeller) -- 20. Those Who Can Fly Without Wings: The Depiction of Ideal Persons in the Inner Chapters of the Zhuangzi (Lin) -- Part 4. Central Concepts -- 21. Confucius as a Literary and Philosophical Figure in the Zhuangzi (Cook) -- 22. The Relation between Laozi and Zhuangzi (Fried) -- 23. Xunzi and Zhuangzi (Ting) -- 24. Zhuangzi and the Logicians (Kwok) -- 25. Zhuangzi and Religious Daoism (Kohn) -- 26. Zhuangzi and Wei-Jin Xuanxue (Lo) -- 27. Zhuangzi and Neo-Confucianism (Tan) -- 28. Zhuangzi and Buddhism (Hong) -- Part 5. Ethics, Value and Knowledge -- 29. Zhuangzi and Normative Ethics (Fraser) -- 30. Internal Sages and External Kings: Moral Pluralism and Happiness in the Zhuangzi (Nam) -- 31. The Value of Spontaneity (Luk) -- 32. Filial Piety in the Zhuangzi—“Let the Parents Forget You” (Chiu) -- 33. How Much Intuition Goes Into Intuitive Skill? (Wong) -- 34. What Do the Skill Masters Know? (Lai) -- 35. Skepticism and Relativism in the Zhuangzi (Sturgeon) -- 36. Zhuangzi from the Neuro-Scientific Perspective (Raphals) -- 37. The Problem of Freedom in the Zhuangzi (Jiang) -- 38. Implied Social and Political Values in the Zhuangzi (Lee) -- Part 6. The Zhuangzi and Western Philosophy -- 39. The “art of sauntering” in the Zhuangzi and in the writings of Henry David Thoreau (Lin) -- 40. Buber, Heidegger and Zhuangzi (Nelson) -- 41. The Cementing and Loosening of Human Bonds in Spinoza and the Zhuangzi (Ozbey) -- 42. The Aesthetic in Kant and the Zhuangzi (Guzowska) -- 43. Zhuangzi's Notion of the True Master and Wittgenstein's Grammatical Investigation (Cheung) -- 44. The Art of Nourishing Life—Philosophical Therapies in the Platonic Dialogues and the Zhuangzi (Sikri) -- 45. Zhuangzi and Nietzsche (Shang) -- 46. Is Zhuangzi a Wanton? A Comparison Between Zhuangzi’s Theory of Freedom and Frankfurt’s Notion of Personhood(Hung).